2015
DOI: 10.1124/dmd.114.061622
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inhibitory and Peroxisome Proliferator-Activated Receptor α–Dependent Modulating Effects of Silybin on Principal Hepatic Drug-Metabolizing Enzymes

Abstract: Silybin, a major pharmacologically active compound in silymarin, has been widely used in combination with other prescriptions in the clinic to treat hepatitis and a host of other diseases. Previous studies suggested that silybin is a potential inhibitor of multiple drug-metabolizing enzymes (DMEs); however, the in vitro to in vivo translation and the mechanisms involved remain established. The aim of this study was to provide a mechanistic understanding of the regulatory effects of silybin on principal DMEs. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
3
18
0
1
Order By: Relevance
“…Silibinin is a well‐known hepatoprotective compound extracted from milk thistle . Reported studies have demonstrated that silibinin inhibited multiple drug‐metabolizing enzymes and confer drug–drug interactions with concomitant drugs …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silibinin is a well‐known hepatoprotective compound extracted from milk thistle . Reported studies have demonstrated that silibinin inhibited multiple drug‐metabolizing enzymes and confer drug–drug interactions with concomitant drugs …”
Section: Discussionmentioning
confidence: 99%
“…17 Reported studies have demonstrated that silibinin inhibited multiple drug-metabolizing enzymes and confer drug-drug interactions with concomitant drugs. 21,22 Silibinin is both a substrate and inhibitor of P-gp, also known as ABCB1 (ATP-binding cassette sub-family B member 1). 23 It has been demonstrated that the polymorphism of ABCB1 C3435T significantly influenced the pharmacokinetics of silibinin in healthy volunteers by increasing its peak plasma concentration and AUC.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis. Western blot analysis was conducted with standard method as previously described 65 . Briefly, protein lysates were separated by SDS-PAGE and transferred to a PVDF membrane, which was then blocked in 5% nonfat milk.…”
Section: Methodsmentioning
confidence: 99%
“…Reporter gene analysis. Cells were transfected with Plin1 luciferase reporter constructs using Lipofectamine 2000 reagent according to the manual instruction and treated with OCA in the absence or presence of SP for 24 h. Cells were lysed and the luciferase activities were measured with the Luc-Pair Duo-Luciferase HS Assay Kit (GeneCopoeia, Rockville, MD, USA) 65 .…”
Section: Methodsmentioning
confidence: 99%
“…Ґени, які кодують синтез ґлутатіон-S-трансфераз (GST), належать до основних, залучених у патоґенез різних хронічних дифузних захворювань печінки (ХДЗП) [40,65]. На адипо-та фіброґенез впливають також ґени, що кодують синтез рецепторів-активаторів проліферації пероксисом (PPAR) [67,71], які відіграють ключову роль у моделюванні синтезу, депонування і транспортування ліпідів і здатні впливати на виникнення й перебіг НАЖХП [36].…”
unclassified